(untitled) (Journal of Human Sciences, 2021)
This study aims to highlight the role that philosophy plays in the educational field as it is an important social and human process that is indispensable to humans because it bears the responsibility of the dynamic side of thought, and at the same time it represents the procedural means to achieve what the thought carries from the cognitive system in all walks of life. It stimulates the mind to investigate and scientific research, exposes the superstitions, illusions and myths that mislead scientific research and the truth, and directs the outputs of science for the public benefit of society. The study also aims to reveal the need for philosophy in confronting issues of peace and sustainable development for the sake of human dignity. To consolidate the values of goodness, justice and tolerance, and to reach enlightening solutions that restore wisdom and rationality to the lost arab mind, which is preoccupied with managing itself, and to find a critical philosophical view that reveals the causes of failure, and engages in the culture of modernity... The culture of change, renewal and innovation, to face crucial challenges in our region through questions. Next: is the absence of philosophy in the school curricula intentional or a spontaneous absence resulting from a cognitive ignorance of the importance of the philosophical role of education? What is the role of philosophy in solving the problems of society? does philosophy as a theoretical science have a role to play in the structure of society? the study concluded that attention should be paid to integrating philosophy into academic curricula and considering it as a subject like other subjects and defending it from the view of discontent and aversion resulting from a lack of awareness of philosophy and ignorance of the value of the task entrusted to it.